2006
DOI: 10.1007/s10555-006-9006-2
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β in cancer and metastasis

Abstract: Transforming growth factor-beta (TGF-beta) is a multifunctional regulatory polypeptide that is the prototypical member of a large family of cytokines that controls many aspects of cellular function, including cellular proliferation, differentiation, migration, apoptosis, adhesion, angiogenesis, immune surveillance, and survival. The actions of TGF-beta are dependent on several factors including cell type, growth conditions, and the presence of other polypeptide growth factors. One of the biological effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
386
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(403 citation statements)
references
References 179 publications
7
386
0
6
Order By: Relevance
“…AGTR1 signaling has been shown to increase the proliferation of stromal and tumor cells and the transcription of inflammatory cytokines and chemokines that promote cancer cell migration and dissemination (49). The reduction in active TGF-β1 levels by RAAS antagonists could also reduce metastasis (50). Consequently, in addition to improving the delivery of antitumor agents, losartan may also inhibit tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…AGTR1 signaling has been shown to increase the proliferation of stromal and tumor cells and the transcription of inflammatory cytokines and chemokines that promote cancer cell migration and dissemination (49). The reduction in active TGF-β1 levels by RAAS antagonists could also reduce metastasis (50). Consequently, in addition to improving the delivery of antitumor agents, losartan may also inhibit tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of TGF-␤1 are produced by many types of tumors and are associated with poor prognosis in cancer patients (32). Large amounts of TGF-␤1 affect the proliferation and differentiation of cells as well as migration, invasion, angiogenesis, and immune surveillance (41). We first demonstrated that overexpression and stimulation of IL-27 inhibit the expression of TGF-␤1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The functional alteration of TGF-␤1 is due to changes in the degree of tumor differentiation and sensitivity to TGF-␤1 (41). High levels of TGF-␤1 are produced by many types of tumors and are associated with poor prognosis in cancer patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…This also appears to protect cancer cells from the toxic actions of chemotherapy and radiotherapy, rendering these treatment modalities less effective. Many epithelial tumor entities including gastric and cervical cancer as well as cancers of head, neck, breast and lung express high levels of EGF, TGF-β1 and TNF-α, which are associated with advanced disease and poor clinical prognosis (Stuelten et al, 2005;Jakowlew et al, 2006;Van et al, 2006;Bussink et al, 2008;Wu et al, 2009). Higher level expression of EGF, TGF-β1 and TNF-α have been inversely correlated to survival in these patients and high expression levels have been found in advanced tumor stages (Friess et al, 1999;Ghaneh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%